Peningkatan Kapasitas Pakan Ternak Melalui Intervensi Teknologi Alat Pemipil Jagung Di Desa Puasana - Sudarsono, Sudarsono; Aminur, Aminur; Aksar, Prinob Aksar; Barata, La Ode Ahmad; Saputra, Jaka Seru Dwi (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2023)
Thematic KKN is a form of community empowerment to increase economic value and shape the character of an entrepreneurial spirit. This service partner is Puasana village, North Moramo District, South Konawe. The partners' problems are (1) the community in Puasana village has not yet implemented corn sheller technology in processing animal feed (2) the target audience partners still have low knowledge and skills in processing animal feed. The method for carrying out service activities consists of socialization, presenting material and demonstrating corn shelling tools to the target audience. The results of this activity are as follows: first, the community is enthusiastic in participating in a series of service activities starting from preparation to testing the tool. Second, the public understands the technology of corn shellers, starting from the working principles, tool components and operating mechanisms. Third, the spirit of entrepreneurship is increasing as measured by the attendance level at each meeting reaching 95%. Keywords: Corn sheller technology, .